EFFICACY COMPARISON OF SUBACROMIAL AND POSTERIOR APPROACH GLENOHUMERAL JOINT INJECTIONS USING TRIAMCINOLONE ACETONIDE IN CASES OF PRIMAR - Khan, Faisal Javed; Ayaz, Saeed Bin; Tassadaq, Naureen; Ahmad, Khalil; Qureshi, Ali Raza; Akhlaque, Uzma (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the efficacy of subacromial and posterior approach glenohumeral joint injections using triamcinolone acetonide in cases of primary adhesive capsulitis.Study Design: Quasi-experimental study.Place and Duration of Study: Pain Clinics of Armed Forces Institute of Rehabilitation Medicine Rawalpindi and Combined Military Hospital Jhelum, from May to Nov 2014 and from Jan to Jul 2019 respectively.Methodology: We included patients with primary adhesive capsulitis in stage 1 and 2. The pain, measured by Numeric Rating Scale and range of motion of the affected joint measured through goniometer before and four weeks after the injection were the study parameters. A 40-mg injection of triamcinolone acetonide was given blindly into the affected shoulder joint through subacromial injection in 45 patients (group A) and posterior glenohumeral injection in 43 patients (group B). Results: Each group had a significant reduction in mean pain score after four weeks of treatment (p